THE CORRELATION BETWEEN DIETARY PATTERNS OF FOOD ANIMAL ORIGIN AND RISK OF BREAST CANCER IN BANDA ACEH - EVA FITRIYANINGSIH; . NURLIANA; UMMU BALQIS (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2014)
The research was aimed to investigate the correlationbetween food animal origin dietary patterns and breast cancer in Banda Aceh. This case-control study compared the dietary pattern of food animal origin  between 45 breast cancer patients and 45 age-matched controls. Six  dietary patterns were difined by food frequency questioner(FFQ): food animal origin, preserved of food animal origin, processing of food, fats andoils, vegetables and fruits patterns. Preserved of food animal origin were significantly associated with the incidence of breast cancer with an odds ratio (OR) 5.86 [95% confidence interval (CI) =1.49-21.65] respectively; p=0.013; while food animal origin, processing of food, fats and oils, vegetables and fruits dietary patterns were not associated with the incidence of breast cancer. The conclusion of the research that salt fish and keumamah  play an important role of the association